Patriarchy and Women's Struggle in Selected Boom and Post-Boom Novels - Pillado, Kim A. (Journal of Language and Literature, 2023)
Women play vital roles and are essential in the progress of a nation, yet the fabrication of gender instituted by patriarchal-modeled societies trivializes, devoices, and devalues the female sex, placing them in domestic positions and subjecting them to violence. As literature becomes the mirror of women's struggle, it also exposes the threats and challenges of patriarchy on women to assert their voice and to be recognized as significant other and not the other. Employing feminism specifically Simone de Beauvoir's 'second sex' concepts, this paper explored and discussed the status of women against the depiction of patriarchy uncovering women denigration in the two boom novels, One Hundred Years of Solitude (2006) by Gabriel Garcia Marquez, and  Recollections of Things to Come (1996) by Elena Garro, and elaborating women empowerment in the two post-boom novels, The House of the Spirits (1993) by Isabel Allende, and Like Water for Chocolate (1992) by Laura Esquivel. The women characters in the boom novels are stereotyped and placed as secondary characters, whereas those in the post-boom have successfully defined themselves and are empowered to reject the patriarchal portrayal of women. Despite the unrelenting debunking of patriarchy, the status of women characters is still inferior compared to their male counterparts. In turn, the four works convey similarities in depicting the era. These narratives have become platforms for women's rediscovery and avenues to re-evaluate the position and status of women; thus, re-securing their value as contributing voice and body in the society.